Cobalt-based nanoparticles prepared from MOF–carbon templates as efficient hydrogenation catalysts. Issue 45 (20th September 2018) - Murugesan, Kathiravan; Senthamarai, Thirusangumurugan; Sohail, Manzar; Alshammari, Ahmad S.; Pohl, Marga-Martina; Beller, Matthias; Jagadeesh, Rajenahally V.
Abstract : Pyrolysis of cobalt-terephthalic acid MOF template on carbon produces highly active and selective cobalt nanoparticles-based hydrogenation catalysts. Abstract : The development of efficient and selective nanostructured catalysts for industrially relevant hydrogenation reactions continues to be an actual goal of chemical research. In particular, the hydrogenation of nitriles and nitroarenes is of importance for the production of primary amines, which constitute essential feedstocks and key intermediates for advanced chemicals, life science molecules and materials. Herein, we report the preparation of graphene shell encapsulated Co3 O4 - and Co-nanoparticles supported on carbon by the template synthesis of cobalt-terephthalic acid MOF on carbon and subsequent pyrolysis. The resulting nanoparticles create stable and reusable catalysts for selective hydrogenation of functionalized and structurally diverse aromatic, heterocyclic and aliphatic nitriles, and as well as nitro compounds to primary amines (>65 examples). The synthetic and practical utility of this novel non-noble metal-based hydrogenation protocol is demonstrated by upscaling several reactions to multigram-scale and recycling of the catalyst.